Recurrence rate of infantile hemangioma after oral propranolol therapy - Frongia, Giovanni; Byeon, Ji-Oun; Mehrabi, Arianeb; Günther, Patrick (European journal of pediatrics, 2021)
Oral propranolol is the treatment of choice for infantile hemangiomas. The growth relapse rate following oral propranolol therapy is not well established in the literature. The present study aimed at determining predictors of growth relapse of infantile hemangiomas after discontinuation of oral propranolol therapy. A retrospective analysis was performed of all cases of infantile hemangiomas aged ≤ 12 months undergoing oral propranolol therapy in a 6-year period. Of the 198 cases, regrowth after oral propranolol therapy was observed in 35 patients (18%). Facial hemangiomas showed a higher (p = 0.003) relapse rate as compared with other hemangiomas (27 out of 107 facial cases vs. 8 out of 91 with other location, respectively 25% and 8.8%). Of 35 growth relapses cases, 66% of cases (23 in total, 18 facial and 5 otherwise located hemangiomas) underwent a second cycle of oral propranolol therapy (median length of treatment 3 months, interquartile range 2-3). All cases had a successful outcome, either after a single cycle oral propranolol therapy (163 cases, 82%), or in case of regrowth, after a second therapy cycle (23 cases, 12%) or further conservative management (12 cases, 6%).
Published: 13 November 2020
Gesehen am 14.09.2021